Continuity of Care (COC) pada Ny L Umur 35 Tahun G2P1A0 di PMB Isnaningsih - Ryan Nabela Maha Rani; Ninik Christiani (Universitas Ngudi Waluyo, 2025)
Continuous midwifery care (continuity of care) is the provision of midwifery care from pregnancy, childbirth, postpartum, neonate until deciding to use family planning. This aims to help monitor and detect the possibility of complications that accompany each mother and baby from pregnancy until the mother uses family planning. The method of midwifery care at PMB Isnaningsih and through home visits by providing counseling according to the mother's needs. Midwifery care provided to Mrs.